Situs inversus in a Dog - Mello, Renata Meira Lopes de Castro; Nassif, Flávia Bormann Vieira; Lima, Flávio Guilherme Costa; Carvalho, Marjane Santos de Matos; Carlos, Renata Santiago Alberto (Acta Scientiae Veterinariae, 2018)
Background: Situs inversus (SI) is a rare congenital malformation characterized by the transposition of the viscera (thoracic and/or abdominal) to the opposite side of its normal topography, as a mirror image. In situs inversus totalis (SIT), all organs are inverted, in addition to the cardiac apex being directed to the right side of the body (dextrocardia). It may not present any clinical signs, and hence, it may be an accidental finding. Because of the rare occurrence of SIT, no epidemiological studies have been conducted in dogs. In 50% of the cases, it may be associated with primary ciliary dyskinesia (PCD), which causes respiratory clinical signs. SIT can be diagnosed using routine examinations such as ultrasonography, radiography, tomography, and echocardiography. The objective of this paper was to describe the radiographic and echocardiographic findings in a dog with SIT. Case: A 4-month-old Yorkshire Terrier bitch was admitted to the veterinary clinic, with a clinical complaint of cough. A physical examination showed that the dog’s general conditions were good; it had normal appetite and the mucous membranes had a normal color. Radiographic examination revealed changes in the topographic anatomy of the organs. The cardiac silhouette was inverted, adopting a “D” form; this suggested that the left-side chambers were positioned on the right side, and the right-side chambers were located in the left topographic region. The aortic arch was visible on the right side of the thorax. A diffuse non-structured pulmonary interstitial pattern was observed on latero-lateral projections, which could be associated with an inflammatory process. The fundic region of the stomach, spleen, and thymus were visible on the right side. The liver was on the left side of the patient’s abdomen. The stomach contained a foreign body of radiopaque nature that was considered a radiographic finding. Echocardiography revealed the right atrium on the left, and the left atrium on the right side. The diagnosis was SIT. The prescribed treatment included prednisolone (1 mg/Kg SID) and Nacetylcysteine (10 mg/kg BID), both for 7 days, based on the possibility of bronchitis. Upon return after medication, the animal showed no clinical signs of cough. After 1 year of SIT diagnosis, the animal has remained asymptomatic and has shown good physical development. Discussion: Dogs with SIT do not usually show clinical signs, and the condition is considered an accidental finding on complementary examinations such as ultrasonography, radiography, tomography, and echocardiography. The radiographic examination associated with echocardiography allowed the identification of SIT, which in this case was not associated with PCD because the respiratory clinical signs had not reappeared after treatment. The prognosis in this case was considered good, corroborating the findings of previous studies showing that the prognosis of individuals with isolated SI is good in the absence of any structural cardiac alteration or other underlying diagnoses, with the average life expectancy being similar to that of the general population. In conclusion, when isolated, SIT is an abnormality that is difficult to diagnose because it does not necessarily present clinical signs. The case reported here contributes to the literature because it documents an accidental finding of an isolated case of SIT in a young dog, which had a good prognosis and quality of life after treatment. Keywords: dog, ciliary disease, inversion of organs.